Birth preparedness and complication readiness among rural women of reproductive age in Abeshige district, Guraghe zone, SNNPR, Ethiopia - Zepre K; Kaba M (Dove Medical Press, 2016)
Kebebush Zepre,1 Mirgissa Kaba2 1Guraghe Zone Health Department, Wolkite, SNNPR, 2School of Public Health, Addis Ababa University, Addis Ababa, Ethiopia Background: Birth preparedness and complication readiness (BPCR) is a strategy that helps women to consider all available maternal health care services during pregnancy and prepare for potential complications. Federal Ministry of Health in Ethiopia has taken steps to roll out the strategy at community level. Yet, women in rural communities still do not make use of available services to avoid complications in connection to pregnancy and delivery. Objective: This study aims to assess the current BPCR practice and determine associated factors among rural women of reproductive age in Abeshige district, Guraghe zone, SNNPR, Ethiopia. Methods: A community-based cross-sectional study was carried out from February to March 2015. A total of 454 women were randomly selected and interviewed using pretested structured questionnaires, while opinion leaders, health extension workers, and selected women in the community were engaged in in-depth interviews and focus group discussions, using checklists prepared to guide the interviews. Data from different sources were analyzed, triangulated, and interpreted to respond to the objectives. Results: Thirty-seven percent of the respondents were found to have prepared for birth and its complications. BPCR was higher among women who lived within a 1-hour walk from a health center (adjusted odds ratio [AOR] =3.51, 95% confidence interval [CI]: 1.78, 36.79) and who were aware of the danger signs of pregnancy (AOR =1.72, 95% CI: 1.78, 2.94) and postpartum complications (AOR =2.32, 95% CI: 1.32, 4.21). A major source of information was found to be health extension workers and one-to-five women networks (AOR =2.81, 95% CI: 1.34, 6.21) and (AOR =2.52, 95% CI: 1.17, 5.54), respectively. Qualitative finding revealed that lack of transportation and concern over cost of services are key barriers to BPCR. Conclusion: BPCR in Abeshige was found to be relatively low, calling for more interventions beyond mere awareness. Availing transportation services and ensuring services free of charge would help in improving BPCR in the study area. Keywords: maternal health, preparing for birth, community level care, safe pregnancy and delivery